ENHANCED SECURITY AUDIO STEGANOGRAPHY BY USING HIGHER LEAST SIGNIFICANT BIT - Surenthiran Krishnan, 1984-, author; Mohd. Shahidan Abdullah, Assoc.Prof.Dr., supervisor; Sekolah Informatiks Termaju (Kuala Lumpur : Universiti Teknologi Malaysia, 2015)
Thesis (Sarjana Sains (Jaminan Maklumat)) - Universiti Teknologi Malaysia, 2015